Exosomes: A Novel Strategy for Treatment and Prevention of Diseases - Wang, Jiaqi; Sun, Xiaoyan; Zhao, Jiayu; Yang, Yang; Cai, Xueting; Xu, Jianguang; Cao, Peng (Frontiers in Pharmacology, 2017)
An “exosome” is a nanoscale membrane vesicle derived from cell endocytosis that functions as an important intercellular communication mediator regulating the exchange of proteins and genetic materials between donor and surrounding cells. Exosomes secreted by normal and cancer cells participate in tumor initiation, progression, invasion, and metastasis. Furthermore, immune cells and cancer cells exert a two-way bidirectional regulatory effect on tumor immunity by exchanging exosomes. Current studies on exosomes have further expanded their known functions in physiological and pathological processes. The purpose of this review is to describe their discovery and biological functions in the context of their enormous potential in the clinical diagnosis, prevention, and treatment of cancer as well as bacterial and viral infectious diseases.